ACR Appropriateness Criteria® Right Lower Quadrant Pain—Suspected Appendicitis. Issue 2 (June 2015) - Smith, Martin P.; Katz, Douglas S.; Lalani, Tasneem; Carucci, Laura R.; Cash, Brooks D.; Kim, David H.; Piorkowski, Robert J.; Small, William C.; Spottswood, Stephanie E.; Tulchinsky, Mark; Yaghmai, Vahid; Yee, Judy; et al.
<x xml:space="preserve">Abstract</x> Abstract The most common cause of acute right lower quadrant (RLQ) pain requiring surgery is acute appendicitis (AA). This narrative's focus is on imaging procedures in the diagnosis of AA, with consideration of other diseases causing RLQ pain. In general, Computed Tomography (CT) is the most accurate imaging study for evaluating suspected AA and alternative etiologies of RLQ pain. Data favor intravenous contrast use for CT, but the need for enteric contrast when intravenous contrast is used is not strongly favored. Radiation exposure concerns from CT have led to increased investigation in minimizing CT radiation dose while maintaining diagnostic accuracy and in using algorithms with ultrasound as a first imaging examination followed by CT in inconclusive cases. In children, ultrasound is the preferred initial examination, as it is nearly as accurate as CT for the diagnosis of AA in this population and without ionizing radiation exposure. In pregnant women, ultrasound is preferred initially with MRI as a second imaging examination in inconclusive cases, which is the majority. The American College of Radiology Appropriateness Criteria® are evidence-based guidelines for specific clinical conditions that are reviewed every three years by a multidisciplinary expert panel. The guideline development and review include an extensive analysis of current medical literature from peer reviewed journals and the application of a well-established consensus methodology (modified Delphi) to rate the appropriateness of imaging and treatment procedures by the panel. In those instances where evidence is lacking or not definitive, expert opinion may be used to recommend imaging or treatment.